PENGARUH KOMPETENSI DAN KEPEMIMPINAN SPIRITUAL TERHADAP MOTIVASI KERJA KARYAWAN - Agus Sugiardi (Al-Amien Prenduan for Islamic Institute, 2021)
This study aims to describe the influence of competence and spiritual leadership on employee motivation. This research is an explanatory research and this research uses SPSS to process sample data of 97 employees of PT Marinal Indo Prima. The results showed that: Competence has a positive and significant effect on employee motivation and spiritual leadership has a positive and significant effect on employee motivation.